Die städtische Produktion von „Armutsmigration“: Soziale Kämpfe um prekäres Wohnen in Frankfurt am Main - Künkel, Jenny (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2018)
In 2013 the spectre of „benefit tourism” entered the German urban agenda as a “poverty migration” discourse. The paper shows how the local state itself creates the scandalized precarious living conditions of EU migrants. Drawing on an interview-based case study of the homelessness politics in Frankfurt am Main it points to a logic of reverse inter-urban competition that aims at deterring „costly“ subjects: By limiting migrants’ access to social benefits and infrastructures such as homeless shelters, cities try to present themselves as bad benefit tourism destinations. Social movements contest the exclusionary politics that produce homelessness and cramped housing. Yet, while successfully putting the topic on the agenda, in Frankfurt, the rights-based approach, demanding shelter for everybody, failed to challenge the city’s legal discourse dividing migrants into il /legal and benefit un /entitled subjects.